Dynamics of swarm intelligence health analysis for the next generation - Suresh Kumar, Arumugam 1979-; Köse, Utku 1985-; Sharma, Sachin 1988-; Nirmal Kumar, S. Jerald 1981- (IGI Global, 2023)
The book discusses the role of people behavioral activity in the evolution of the traditional medical system to an intelligent system. It is based on the development of technical improvements considered in the process of intelligent systems by using cognitive techniques, swarm Intelligence deep learning, and machine learning techniques. These techniques will be used for multimodal biomedical data processing and non-invasive interpretation which efficiently improves the patient interpretation quality. Moreover, it objects to highlight the challenges of developing and proposing new ideas regarding the out-ofhospital dedicated systems directions. Solicits contributions of this book include theory, applications, and design schemes of intelligent systems, vision techniques, and biomedical applications, as well as the methodologies behind them. This book also focuses on the economic, social, and environmental impact of swarm Intelligence smart healthcare systems. It aims to provide a detailed understanding of swarm Intelligence analysis supported applications while engaging premium smart computing methods and improved intelligent algorithms in the field of computer science. Further, the detailed assessment of IoT sensors, actuators, communication, and computing technology, and standards has been taken into considerations. Emphasis is also laid on the challenges associated with these smart healthcare systems. It includes connectivity, sensing, computation, complexity, and security issues. Therefore, this book designed for new innovations to overcome such challenges and to explore the dynamics of swarm Intelligence health analysis for the future generation. We hope to strengthen the link between the Swarm Intelligence analysis sector and mental health research in this book chapter. Various works in the digital health arena shown how real-time monitoring of mood disorders improved the overall quality of life of patients and citizens
Keywords: Medical informatics; Swarm intelligence